Synchrotron X-ray nano computed tomography based simulation of stress evolution in LiMn2O4 electrodes. (1st September 2017) - Ghorbani Kashkooli, Ali; Foreman, Evan; Farhad, Siamak; Lee, Dong Un; Ahn, Wook; Feng, Kun; De Andrade, Vincent; Chen, Zhongwei
Abstract: In this study, synchrotron X-ray nano-computed tomography at Advanced Photon Source in Argonne National Laboratory has been employed to reconstruct real 3D active particle morphology of a LiMn2 O4 (LMO) electrode commonly used in lithium-ion batteries (LIBs). For the first time, carbon-doped binder domain (CBD) has been included in the electrode structure as a 108 nm thick uniform layer using image processing technique. With this unique model, stress generated inside four LMO particles with a uniform layer of CBD has been simulated, demonstrating its strong dependence on local morphology (surface concavity and convexity), and the mechanical properties of CBD such as Young's modulus. Specifically, high levels of stress have been found in vicinity of particle's center or near surface concave regions, however, much lower than the material failure limits even after discharging at the rate as high as 5C. On the other hand, the stress inside CBD has reached its mechanical limits when discharged at 5C, suggesting that it can potentially lead to failure by plastic deformation. The findings in this study highlight the importance of modeling LIB active particles with CBD and its appropriate compositional design and development to prevent the loss of electrical connectivity of the active particles from the percolated solid network and power losses due to CBD failure.